A case of Raynaud's phenomenon of toes induced by whole‐body warm stimulation. (21st October 2021) - Akimoto, Takashi; Kobayashi, Tadashi; Maita, Hiroki; Osawa, Hiroshi; Kato, Hiroyuki
Abstract: Raynaud's phenomenon, induced by cold stimulation and emotional stress, is also induced by whole‐body warm stimulation. A 74‐year‐old man was referred to our department because of nocturnal toe pain from 2 years prior and immediate color change of the toes from 1 year prior when submerging himself into a warm bath. Physical examination and blood tests revealed no abnormal findings suggestive of secondary Raynaud's phenomenon. Two years later, the signs and symptoms persisted. When physicians confirm Reynaud's phenomenon, they should check for the possibility of secondary Reynaud's phenomenon. Additional research on Reynaud's phenomenon induced by warm stimulation is needed. Abstract : Raynaud's phenomenon, induced by cold stimulation and emotional stress, is also induced by whole‐body warm stimulation. A 74‐year‐old man was referred to our department because of nocturnal toe pain from 2 years prior and immediate color change of the toes from 1 year prior when submerging himself into a warm bath. Additional research on Reynaud's phenomenon induced by warm stimulation is needed.